PROFILE OF WHITE BLOOD CELLS IN BALI CATTLE NATURALLY INFECTED BY DERMATOPHYTOSIS - Nurani, Nirae Nirae; Putriningsih, Putu Ayu Sisyawati; Arjentinia, I Putu Gede Yudhi (Buletin Veteriner Udayana; Vol. 9 No. 1 Pebruari 2017, 2017)
Dermatophytosis is kind of disease which caused by dermatophyta fungus. White blood cell (leukocyte) will responds every strange things which entering the body as a defend cell. In Indonesia, only few information of the white blood cell (leukocyte) in the Dermatophytosis cases towards balinese cattle can be found. The purpose of the research in finding the comparasion between lukocyte of normal balinese cattle which is not infected and balinese cattle which infected by dematophyta fungus. The research are using 12 samples of blood, is abaout 6 blood’s sampel from normal balinese cattle and 6 blood’s sample of balinese cattle which is infected by dermatophyta fungus.  The first attempt is checking the skin scratching and the hair with 10% of KOH liquid. Sabouraud’s Dextrose Agar (SDA) is used for isolate and identified dermatophyta fungus. Calculation and checking the total of leukocyte are using hemasitometer, while Giemsa liquid are using for differential leukocyte. T-Test shows the real differences between them which in to balinese cattle which infected by dermatophytosis. The analyzes result bye the statistic data using Mann-Whitney Test is showing there is real difference to balinese cattle’s monocyte which infected by dermatofitosis. There is a normal difference between balinese cattle which is normal and infected. Balinese cattle which infected dermatophyta fungus have a total of leukocyte and monocyte are higher than normal balinese cattle.
Keywords: sapi bali; dermatofitosis; leukosit